Nabataty - Aya Daraghma; Sahar Abdelhaq (My University, 2023)
In today's fast-paced world, the allure of greenery and nature remains constant, and so does the need for convenient access to plants and gardening essentials. This graduation project presents an innovative solution in the form of a mobile application and website for a plant store, designed to cater to the evolving needs of plant enthusiasts. The platform offers a user-friendly interface, allowing customers to explore and purchase a wide variety of plants with ease. Users can filter their plant selections by choosing between indoor and outdoor plants, ensuring they find the perfect fit for their space and preferences. Moreover, the application provides a unique feature that enables users to create personalized plant gifts. This includes selecting the type of pots, packaging method, and other custom details to craft a thoughtful and aesthetically pleasing gift. One of the standout features of our application is its plant diagnosis functionality. Users can simply photograph their plants, and the application provides real-time information about the plant's condition and recommends suitable fertilizers, promoting healthy plant care practices. In addition to plant offerings, our store includes various agricultural tools and accessories to support customers in their gardening endeavors. To further enhance convenience, a credit payment method is integrated into the platform, ensuring a seamless and secure shopping experience. This graduation project not only demonstrates the fusion of technology and horticulture but also addresses the growing demand for accessible and comprehensive solutions in the realm of plant care and gardening. Our mobile application and website aim to make plant shopping an enjoyable and informative experience